Clinical Outcome Following Induction of Labour with Misoprostol (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Induction of labour in the third trimester of pregnancy may be considered beneficial in many clinical circumstances.Objective: The aim of this study was to find the effectiveness and safety of a novel dosing regimen of oral misoprostol in a Bangladeshi sample.Methods: A cross sectional study was conducted in the Department of Obstetrics and Gynecology, Sir Salimullah Medical College & Mitford Hospital, Dhaka from October 2008 to September 2009 based on the guideline of American College of Obstetricians and Gynecologists. Fifty nine cases were enrolled according to inclusion criteria by clinical pelvimetry and bishop scoring. Contracted pelvis, evidence of cephalopelvic disproportion, placenta previa, unexplained vaginal bleeding, grand multipara, fetal malpresentation, previous uterine scar and fetal distress cases were excluded. Misoprostol was administered per orally. Maternal outcome was assessed by normal vaginal delivery, caesarean section, maternal distress, perineal tear, cervical tear, uterine hyper-stimulation and fetal outcome was assessed in the form of fetal distress, meconium stained amnions, neonatal admission, perinatal death and no complication. Statistical analysis was done using SPSS v 13. Probability value was set at P